Assessment of ADMA, estradiol, and progesterone in severe preeclampsia. (18th May 2016) - Zheng, Jing-Jie; Wang, Hai-Ou; Huang, Min; Zheng, Fei-Yun
ABSTRACT: Background : Decreased nitrous oxide (NO) levels are crucial factors in severe preeclampsia (sPE), and asymmetric dimethylarginine (ADMA) is an endogenous inhibitor of NO synthetase. Steroid hormones are closely related to the vascular endothelium. This study determined the levels of and correlations between ADMA, estradiol (E2), and progesterone (Pg) in sPE to investigate the roles of these factors in this disease. Methods : Sixty-two sPE patients (sPE group) were divided into the sPE1 subgroup (28 +1 –32 +0 weeks of pregnancy), the sPE2 subgroup (32 +1 –36 +0 weeks), and the sPE3 subgroup (36 +1 –40 +0 weeks) and 75 normal pregnant women (NC group) were divided into the NC1 subgroup (28 +1 –32 +0 weeks of gestation), the NC2 subgroup (32 +1 –36 +0 weeks), and the NC3 subgroup (36 +1 –40 +0 weeks). Serum and placental ADMA levels were measured by enzyme-linked immunosorbent assay (ELISA), and serum E2 and Pg concentrations were determined by the chemilumineseent immunoassay (CLIA). Results : ADMA concentrations in both the placenta and the maternal serum were significantly higher in the sPE group ( p < 0.05). Higher ADMA contents were observed in the placenta relative to the maternal serum ( p < 0.05). Serum E2 levels were significantly lower in the sPE group ( p < 0.05). For Pg, the only significant difference was observed between the sPE1 and NC1 subgroups ( p < 0.05). The Pg/E2 ratios in the sPE groups were significantly higher, with a significant high positive correlation between Pg/E2 ratios and serum ADMA levels. Conclusion : Increased serum levels of ADMA in sPE may result from increased secretion from the placenta, and the increased Pg/E2 ratio may play a role in the development of sPE by aggravating ADMA.